DETERMINANTS OF AUDIT REPORT LAG WITH AUDITOR SPECIALIZATION MODERATION - Aisyah Rahmawati; Mohamad Zulman Hakim (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2026)
Audit report lag (ARL) poses a persistent problem within the property and real estate sector, as prolonged reporting timelines can compromise the relevance and reliability of financial disclosures for investors and other users. The purpose of this research is to analyze the impact of audit tenure, financial distress, audit fees, and company complexity on Audit Report Lag, with auditor specialization as a moderating variable. The study employs a quantitative research methodology using secondary data obtained from the annual financial statements of listed property and real estate companies in Indonesia for the period 2020-2024. The final sample comprises 32 firms, yielding 160 firm-year observations. Data analysis is conducted using multiple regression. Results show that audit tenure and company complexity have a significant negative effect on ARL, while financial distress and audit fees have no direct significant impact. Auditor specialization is found to moderate the effects of audit fees and company complexity on ARL, but not those of audit tenure or financial distress. These patterns are explained through Agency Theory and Signaling Theory, which respectively address supervisory alignment and informational signaling. The research concludes with recommendations for auditors, company executives, investors, and policymakers to foster timely and efficient financial reporting.